Morality, Altruism, and Occupation Choice: Theory and Evidence - Sanjit Dhami; Mengxing Wei; Pavan Mamidi (Center for Economic Studies and ifo Institute (CESifo), 2022)
We consider a private sector job that offers high-powered incentives and two public sector jobs that produce an identical public good, but only one of them offers opportunities for corruption. Our theoretical predictions relate occupation and effort choices, in these three jobs, to preferences for altruism and morality that are structurally estimated. The predictions are tested in pre-registered experiments. We also estimate proxies for altruism/morality from the dictator/die-rolling games. We demonstrate the mutual portability of parameters between both sets of games. Those choosing the private sector job use a simple heuristic of maximizing legal monetary payoffs, but they are not less altruistic or less moral; they exhibit context dependent preferences. Conditional on choosing the public sector, less moral subjects are more likely to choose the corrupt public sector job. The effects of altruism on occupational choice are subtle, but altruism positively influences the effort choices in the public sector. The majority of subjects choose the corrupt public sector job, but effort is highest in the private sector. On average, corruption increases the size of the public sector, although the public output received by society is identical in both public sector jobs.
Keywords: D01; D91; 330; morality; altruism; institutional corruption; occupational choice; effort choice; portability of behavioural parameters